(untitled) (Circe de clásicos y modernos, 2020)
The aim of this study is to analyze the passages about μετάνοια in Philo’s texts, with special attention to the section concerning this subject in On the virtues 175-186, in order to determine what value do repentance and conversion hold for the Jewish philosopher, in which ways they are produced and expressed, and what are their effects from a moral and an eschatological point of view.